Bioinspired multilayer multiscale architectures into PDMS for simultaneously enhancing the thermal conductivity and flame retardancy. (10th November 2022) - Li, Qinglan; Song, Shiqiang; Yang, Haowen; Wang, Jincheng; Xiao, Jianhua; Zhang, Yong
Abstract: Combing high thermal conductivity and excellent flame retardancy is crucial for the development of thermal management composites. Herein, we report a bioinspired multilayer multiscale architecture comprising nanoscale MXene as the protective layer 1, atomic Cu 2+ coordination molecular scale dendritic PEI as the protective layer 2 and encapsulated flammable PDMS as a matrix. Upon exposure to flame, the two layers can hinder polymer combustion, wherein MXene nanosheets and PEI-Cu serve as a barrier and thermally conductive layers, as well as catalytic and adsorption layers, respectively. As a result, the as-prepared PDMS composites exhibit a high out-of-plane thermal conductivity of ∼0.60 W m −1 k −1, a reduced heat release rate and extremely low smoke (CO and CO2 ) generation at low filler loadings, suggesting excellent smoke suppression and toxicity reduction. This study provides a new strategy for the development of polymer composites with high thermal management capabilities and excellent flame retardancy. Graphical abstract: Image 1